Optimal Design and Analysis of Traction Steering Mechanism for Loading Transport Vehicle - Ruochao Wang; Zhikuan Yin; Zisheng Liu; Zijue Wang; Taiming Zhang; Jiantao Yao (Jixie chuandong)
At present， parallelogram traction steering mechanism is mostly adopted in traction vehicles used in warehousing cargo loading and transfer. Because the steering mechanism does not conform to Ackermann's principle， the sliding friction force is large when steering， which will lead to traction and steering operation laborious. A trapezoidal traction steering mechanism based on Ackerman principle is designed， and uses the sequential quadratic programming genetic algorithm in multivariate nonlinear programming to optimize the specific dimensions of the trapezoidal traction steering mechanism， the size parameters which more satisfy the Ackerman principle are obtained. A prototype is made based on the optimized parameters. By using the Adams dynamics simulation software， the simulation and comparative experiment of the trapezoidal steering mechanism with the optimized parallelogram mechanism from three dimensions of steering trajectory， steering start torque， and energy conversion efficiency are carried out. The analysis results show that the optimized mechanism has a smoother steering trajectory， smaller steering starting torque and higher energy conversion efficiency.